DETERMINANTS OF SYSTEMATIC AND UNSYSTEMATIC LIQUIDITY RISK IN ISLAMIC BANKS - Anwar Hussain; Ploypailin Kijkasiwat; Bushra Mobeen Ijaz; Fitim Deari (Journal of Islamic Monetary Economics and Finance, 2022)
This study examines whether systematic (macroeconomic) and unsystematic (bank specific) factors determine liquidity risk in Islamic banks. The study employs a sample of Islamic banks from Pakistan, Qatar, Malaysia, UAE, Bangladesh, Bahrain, and Saudi Arabia over the period 2008 – 2019. Using Least Square estimation methods to estimate the model separately for each country, we find the results to be mixed and different across countries. The results also show that non-performing loans, bank size, leverage ratio and return on assets are key unsystematic drivers in determining the liquidity risk of Islamic banks. This study points out the fragility of Islamic banks in relation to managing liquidity risk.